An evaluation of the housing materials loan program of the Tondo foreshore- Dagat-Dagatan development project - Reforma, Mila A. (Philippine Journal of Public Administration, 1979)
An evaluation of the Housing Materials Loan Program (HMLP) which was designed to support the Tondo Foreshore Dagat-Dagatan DevelopmentProject (TFDDP) through the extension of financial assistance to project recipients was conducted with the following objectives: (1) to describe its present administration and performance, (2) to describe the perception of its recipients, (3) to identify the problems confronting it and propose policy options for modifications, and (4) to assess the degree of its success or failure. Using appropriateness, adequacy, efficiency, and effectiveness as the criteria for assessment, the study disclosed that the HMLP as a support program is appropriate but has had mixed ratings as regards its adequacy, efficiency, and effectiveness.